PENGUJIAN KEWAJIBAN MORAL DAN BIAYA KEPATUHAN TERHADAP KEPATUHAN WAJIB PAJAK - I Nyoman Putra Yasa (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
This research aims to know the influence of moral obligation and the cost of compliance with taxpayer compliance. Research done by the method of survey through the dissemination of questionnaires to taxpayers people personal at tax service office (kpp) east of denpasar. Further data obtained were analyzed quantitatively using SPSS assistance 16. Research results show that the positive effect significant moral obligation towards the taxpayer compliance, while the costs of compliance negative effect against a compliance by tax payers.